Application of Steam and Scientific Approaches in Various Learning Models - Alwafa Refinning Anida Setyawan (Jurnal Impresi Indonesia, 2024)
Competitive and productive are the keys to victory to become a developed country, this is the basic capital for the Indonesian people to win the global battle and this has been owned since the time of our ancestors. This study aims to analyze the effectiveness of applying the STEAM (Science, Technology, Engineering, Arts, and Mathematics) approach in various learning models and examine its impact on students' creativity, initiative, and innovation. The application of STEAM learning with an integrated implementation with the application of application-based science fields in children's daily lives through a scientific approach, thus enabling learners to create, take initiative, and innovate individually, because STEAM content is learning with cross-disciplinary connections through exploration opportunities so that it is expected that there is a link between science, technology, engineering, arts, and mathematics by utilizing existing facilities in the surrounding environment to solve problems in building positive knowledge.